Analysis of SPBE and SWCSF measurement instruments using Flesch Reading Ease for state security (Defense and Security Studies, 2023)
The world has transitioned into a digital era where both individuals and governments require technology and the internet. The number of cybercrimes perpetrated online is impacted by the rising usage of computers and the internet. A measurement instrument that can stop cybercrime is necessary. The Six-Ware Cyber Security Framework (SWCSF) and the Electronic-Based Government System (SPBE) are two measurement tools that are expected to be able to stop cybercrime from happening in an agency or organization. But are all people able to use these two instruments? This research was conducted to answer this question by analyzing readability on the SPBE and SWCSF instruments using the Flesch Reading Ease method. The results show that the two instruments were extremely difficult for respondents of all grade levels to comprehend, with the exception of those at the university level or individuals who worked with computers, the internet, and other technologies.